La protección de la persona con discapacidad intelectual como víctima del delito en el Código Penal = The protection of the person with intellectual disability as a victim of criminal offences in the Penal Code - Casanueva Sanz, Itziar (Oñati Socio-Legal Series, 2025)
This paper makes a detailed study of the precepts in which the Penal Code considers in a special way people with intellectual disabilities as victims of crime, limiting ourselves to the cases in which the victim is of legal age. Firstly, we will present the social model of disability and intellectual disability from which we start and, subsequently, these precepts will be analysed, emphasizing the different expressions that the legislator uses to refer to victims with intellectual disabilities in order to determine whether or not they refer to the same reality. Likewise, we will try to give content to these expressions and propose, if necesary, the appropriate lege lata and lege ferenda proposals.